Proposal for an inter-municipal consortium in the health micro-region of Teófilo Otoni/Malacacheta for urban solid waste management (Research, Society and Development, 2021)
The growth of the world population, mainly in the urban area, combined with the exacerbated consumption of goods and services, triggers an increase in the generation of urban solid waste (USW) and thus constitutes a major environmental problem. To follow global environmental public policies and seek to mitigate damage to the environment in Brazil, Law 12,305 of 2010 was instituted, which defined the National Policy on Urban Solid Waste (PNRS), which must be followed by all municipal managers. The aim of the study is to analyze the possibility of developing an inter-municipal consortium in the health microregion of Teófilo Otoni/Malacacheta for the management of MSW. This research is classified as qualitative, with descriptive purpose, adopting bibliographic and documentary procedures to carry out the survey of information related to the study, in order to verify the possibility of implementing an inter-municipal consortium for the management of MSW in that micro-region. The article is structured in the following sections: introduction, problem and research objectives; Theoretical Reference; methodology; final considerations and references. It is concluded that it is urgent to prepare an inter-municipal proposal for Integrated Urban Solid Waste Management (GIRSU), in order to provide a public and/or private partnership that solves the problem of landfills in this region in a short period of time. A dialogue strategy between municipal managers is necessary. Among the discussions to raise awareness of municipal managers, in addition to sustainability and environmental issues, they should be made aware that, in addition to the resources received by the consortium, there are other sources of revenue for the implementation of a GIRSU that will guide the new model environmental education for the population, which can promote income for agents involved in the segregation of waste recycling, in addition to protecting the environment of the micro-region.